Distinct Patterns of University Students Study Crafting and the Relationships to Exhaustion, Well-Being, and Engagement - Mülder, Lina Marie; Schimek, Sonja; Werner, Antonia Maria; Reichel, Jennifer L.; Heller, Sebastian; Tibubos, Ana Nanette; Schäfer, Markus; Dietz, Pavel; Letzel, Stephan; Beutel, Manfred E.; Stark, Birgit; Simon, Perikles; et al. (Frontiers in Psychology, 2022)
Job crafting has been established as a bottom-up work design instrument for promoting health and well-being in the workplace. In recent years, the concepts of job crafting have been applied to the university student context, proving to be positively related to student well-being. Building on person-centred analyses from the employment context, we assessed study crafting strategy combinations and the relationships to student health and well-being. Data from 2,882 German university students were examined, collected online during the summer of 2020. Using latent profile analysis, we found five distinct crafting groups, which showed partial relationships to different levels of emotional exhaustion, engagement, and well-being. The results underscore the positive role of study crafting for student health and well-being. They also further illustrate the less important role of increasing social resources in emotional exhaustion when combined with a moderate increase in structural resources and a moderate increase in challenging demands. Our findings imply that interventions to promote study crafting should be considered to promote student health and well-being.